Encapsulation of Phase Change Materials via Interfacial Miniemulsion Polymerization for High Thermal Energy Storage Density. Issue 3 (30th January 2022) - Zhao, Yuhai; Luo, Yingwu
Abstract: Phase change material (PCM) capsules have potential applications as a thermal management material in energy‐efficient buildings. It is desirable for PCM capsules to have high core‐loading and sub‐micrometer particle size. Herein, it is reported that interfacial reversible addition‐fragmentation chain transfer (RAFT) miniemulsion polymerization can be a convenient method to synthesize high PCM loading polymeric capsule latex. It is found that increasing particle size should be helpful to obtain well‐defined capsules of high PCM loading but post‐addition of surfactant should be carried out to remain the colloidal stability during polymerization. In the case of high PCM loading, a limiting conversion is observed. Increasing crosslinker (DVB) level up to 20 wt% based on monomers can increase the limiting conversion up to 94%. The well‐defined paraffin capsules of 365 nm in diameter is synthesized with 67 wt% PCM loading. The paraffin capsules have a crystallization/melting heat around 105 J g −1 . Replacing paraffin with pure n‐octadecane, the crystallization/melting heat is increased up to 144 J g −1 . Abstract : Interfacial miniemulsion polymerization is extended to synthesize high core‐loading and sub‐micrometer polymeric capsules. The well‐defined capsules of 365 nm in diameter with high conversion is synthesized with 67 wt% core loading. The encapsulated n‐octadecane capsules have a latent heat around 144 J g −1 . This technique has great potential in energy‐efficient buildings and carbon emission reduction.